Prevalence of chronic complications of type 2 diabetes mellitus in outpatients - a cross-sectional hospital based survey in urban China - Liu, Zhaolan (BioMed Central, 2010)
BACKGROUND: Chronic complications are the major outcome of type 2 diabetes mellitus progress, which reduce the quality of life of patients, incur heavy burdens to the health care system, and increase diabetic mortality. The aims of this study were to describe the prevalence of chronic complications among urban Chinese type 2 diabetic outpatients; and to analyze the associations between chronic complications and patients' demographics, diabetic related clinical characteristics. METHODS: This cross-sectional hospital-based study was carried out in 4 major Chinese cities: - Shanghai, Chengdu, Beijing and Guangzhou. The survey was conducted from March to July in 2007 among 1,524 type 2 diabetic outpatients. The subjects were interviewed face-to-face by trained interviewers using a questionnaire to capture information on demographics, disease presentations and complications. All the subjects were invited to have a HbA1c test free of charge by the standardized method with Bio-Rad Variant II. RESULTS: Of the 1,524 study subjects, 637 (41.8%) were male, and the mean age was 63.3 ± 10.2 years. At least one chronic complication was diagnosed in 792 individuals (52.0%) of the study subjects; 509 (33.4%) presented with macrovascular complications and 528 (34.7%) with microvascular complications. The prevalence of cardiovascular and cerebrovascular conditions, neuropathy, nephropathy, ocular lesions and foot disease were 30.1%, 6.8%, 17.8%, 10.7%, 14.8% and 0.8%, respectively. The prevalence of chronic complications varied between cities, and significantly increased with age and duration of diagnosed diabetes. The mean of HbA1c in diabetic patients with chronic complications was 8.2% ± 1.6% and 63.0% of the subjects with type 2 diabetes related complications had a poor glycemic control with the HbA1c > 7.5%. CONCLUSIONS: Chronic complications are highly prevalent among type 2 diabetic outpatients, the glycemic control of diabetic patients with chronic complications was poor, and future efforts should be directed at intensive blood glucose control, strengthening early diagnosis and improving case management to prevent and minimize the occurrence of complications.